Influence of MQL on performance evaluation of EN19 steel under centreless grinding. Issue 14 (26th October 2022) - Arun kumar, N.E.; Suresh Babu, A.; Subramanian, M.; Arunkumar, N
ABSTRACT: Developments in the evolution of manufacturing processes have directed their focus toward machining sustainability. A majority of manufacturing processes utilize a huge quantity of coolant to attain the desired surface finish. The process of grinding is a procedural example that requires a large amount of water to be mixed with the oil in order to produce an emulsion. Furthermore, grinding procedures such as centerless grinding necessitate a high rate of coolant flow to maintain workpiece quality. Minimum quantity lubrication (MQL) is an alternate fluid reduction method used in machining that reduces lubricant quantities to a higher extent. It also facilitates the nonspreading of cutting fluids around the work area, thus resulting a cleaner workplace. This work explicits the analysis of surface finish and roundness of EN19 steel grinding with three different machining conditions, namely, dry, wet, and MQL conditions. The results showed that by using MQL, the surface finish is closer to wet machining with reduced coolant usage and has a cleaner workplace.